Skin Conductance Reactivity as a Predictor of Stroke-Induced Posttraumatic Stress Disorder Symptoms: A Dimensional Approach - Meinhausen, Corinne; Sanchez, Gabriel J.; Edmondson, Donald; Kronish, Ian M.; Schwartz, Joseph E.; Hinrichs, Rebecca; Jovanovic, Tanja; Sumner, Jennifer A. (Depression and Anxiety, 2023)
Background. Posttraumatic stress disorder (PTSD) symptoms can develop following acute, life-threatening medical events. This study explores a potential biomarker of PTSD risk that is novel to a medical trauma population: a noninvasive, mobile skin conductance (SC) measurement. Methods. Participants (n=64) were enrolled inhospital following a stroke or transient ischemic attack (TIA). Mobile measurement of SC reactivity to recalling the stroke/TIA traumatic event was conducted at hospital bedside in the days following the stroke/TIA. PTSD symptoms that developed in response to the stroke/TIA were measured at 1-month follow-up. We tested the association between SC reactivity and total 1-month PTSD symptoms, as well as PTSD symptom dimensions of fear and dysphoria. Results. In unadjusted analyses, there were significant positive associations between inhospital SC reactivity to recalling the stroke/TIA traumatic event and higher-order fear-related symptoms (r=.30, p=.016), as well as lower-order fear-related symptoms of anxious arousal (r=.27, p=.035) and avoidance (r=.25, p=.043) at 1 month. Associations between SC reactivity and the fear, anxious arousal, and avoidance symptom dimensions remained significant in multivariable regression models that adjusted for relevant covariates including age, gender, stroke severity, medical comorbidity, and psychosocial factors. Although there was a positive association observed between SC reactivity to recalling the stroke/TIA event and total PTSD symptom severity at 1-month follow-up, it did not reach the level of statistical significance (r=.23, p=.070). Further, no significant association was detected for dysphoria-related symptoms (r=.11, p=.393). Conclusions. This is the first study to test the prospective association of SC reactivity with PTSD symptom development following a medical trauma. The findings indicate that mobile measures of SC reactivity may be useful for inhospital identification of individuals at risk for fear-related PTSD symptom development following a medical event and highlight the potential mechanisms involved in the development of these symptoms following a medical event.